MESSAGING IN STAINLESS STEEL PLATES - Rojas L., Oswaldo (2002)
This article deals with a project developed pursuing two parallel subjects: one, the analysis of production processes in small and micro enterprises (Pymes) that make stainless steel domestic goods, and two, the design and manufacturing of prototype products. A characteristic of the pymes sector is that their processes are based on plastic misshaping, thus obtaining middle?quality products, revolution geometric shapes, and little complexity; this is eminently a handmade process.